Carboniferous tectonic configuration of the Yining Massif in Western Tianshan, NW China. (25th July 2018) - Li, Yongjun; Xu, Qian; Yang, Gaoxue; Wang, Ran; Tong, Lili; Li, Ganyu; Shen, Rui; Li, Zhao; Wang, Zuopeng; Wang, Zhenyu
Abstract : The tectonic evolution and configuration of the Carboniferous trench‐arc‐basin system (TABS) in the Yining Massif (Western Tianshan, NW China) have long been controversial. The question of the existence of an ancient ocean basin and its subduction polarity is crucial to address this issue. In this study, we suggest that the Early Carboniferous calc‐alkaline volcano‐sedimentary rocks were formed in a fore‐arc/back‐arc basin system, whereas the Late Carboniferous bimodal volcanic rocks and their associated sedimentary rocks were formed under a continental rift setting after the Junggar‐Tarim collision. We propose that the Southern Tianshan ocean basin may have closed in the Late Early Carboniferous, terminating the TABS at Yining. Spatial–temporal distribution of volcanic‐sedimentary rock assemblages suggests that the Early Carboniferous Southern Tianshan ancient ocean basin was similar to the TABS system of the present‐day Japanese island arc.